If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 24 + -8x = 1 + -11x Solving 24 + -8x = 1 + -11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11x' to each side of the equation. 24 + -8x + 11x = 1 + -11x + 11x Combine like terms: -8x + 11x = 3x 24 + 3x = 1 + -11x + 11x Combine like terms: -11x + 11x = 0 24 + 3x = 1 + 0 24 + 3x = 1 Add '-24' to each side of the equation. 24 + -24 + 3x = 1 + -24 Combine like terms: 24 + -24 = 0 0 + 3x = 1 + -24 3x = 1 + -24 Combine like terms: 1 + -24 = -23 3x = -23 Divide each side by '3'. x = -7.666666667 Simplifying x = -7.666666667
| 4-2(3x-5)+x=7(1-3x) | | 1/3h+4=8 | | y=(x-4)/5 | | 3-2(x-1)+4x=5-(2-x) | | -2/3(6x-12y) | | 9(t-9)-11=-6t+10 | | 5w+2=-1+3(w-10) | | X/3-21=14 | | 4-2(3x-5)+x=7-(1-3x) | | X/6-17=14 | | 3x-2(x+4)=2x-3 | | 5x+-5=20 | | 8W+2W-7=23 | | 7+4x-4t=-11 | | 19x-13=25 | | 8x-2+3x=5x+10 | | (2+(2-(2+(2-(2+r)))))=1 | | -7y-2=-6y-6 | | 3(2+5x)+3=2(1-3x) | | 2x+3(1x-10)=45 | | (x^2+1)= | | 2x+3(x-10)=-45 | | y=-0.2*x+520.4 | | 1x-5(x+2)=26 | | 6*6+7= | | 2sen^2x-senx-1=0 | | 5/678 | | 5/6.35 | | 5/6•35 | | 2y-50+5y-17=180 | | 3=5-3/4 | | 5x-8(x+5)= |